Effects of different classroom temperatures on cardiac autonomic control and cognitive performances in undergraduate students. (3rd June 2019) - Barbic, F; Minonzio, M; Cairo, B; Shiffer, D; Dipasquale, A; Cerina, L; Vatteroni, A; Urechie, V; Verzeletti, P; Badilini, F; Vaglio, M; Iatrino, R; et al.
Abstract: Objective : Indoor microclimate may affect students' wellbeing, cardiac autonomic control and cognitive performance with potential impact on learning capabilities. To assess the effects of classroom temperature variations on the autonomic profile and students' cognitive capabilities. Approach : Twenty students attending Humanitas University School, (14M, age 21  ±  3 years) underwent a single-lead ECG continuous recording by a portable device during a 2 h lecture when classroom temperature was set 'neutral' (20 °C–22 °C, Day 1) and when classroom temperature was set to 24 °C–26 °C (Day 2). ECGs were sent by telemetry to a server for off-line analysis. Spectral analysis of RR variability provided indices of cardiac sympathetic (LFnu ), vagal (HF, HFnu ) and cardiac sympatho-vagal modulation (LF/HF). Symbolic analysis of RR variability provided the percentage of sequences of three heart periods with no significant change in RR interval (0V%) and with two significant variations (2V%) reflecting cardiac sympathetic and vagal modulation, respectively. Students' cognitive performance (memory, verbal comprehension and reasoning) was assessed at the end of each lecture using the Cambridge Brain Sciences cognitive evaluation tool. Main results : Classroom temperature and CO2 were assessed every 5 min. Classroom temperatures were 22.4 °C  ±  0.1 °C (Day 1) and 26.2 °C  ±  0.1 °C (Day 2). Student's thermal comfort was lower during Day 2 compared to Day 1. HR, LF/HF and 0V% were greater during Day 2 (79.5  ±  12.1 bpm, 6.9  ±  7.1 and 32.8%  ±  10.3%) than during Day 1 (72.6  ±  10.8 bpm, 3.4  ±  3.7, 21.4%  ±  9.2%). Conversely, 2V% was lower during Day 2 (23.1%  ±  8.1%) than during Day 1 (32.3%  ±  11.4%). Short-term memory, verbal ability and the overall cognitive C -score scores were lower during Day 2 (10.3  ±  0.3; 8.1  ±  1.2 and 10.9  ±  2.0) compared to Day 1 (11.7  ±  2.1; 10.7  ±  1.7 and 12.6  ±  1.8). Significance : During Day 2, a shift of the cardiac autonomic control towards a sympathetic predominance was observed compared to Day 1, in the presence of greater thermal discomfort. Furthermore, during Day 2 reduced cognitive performances were found.